Analisis Pengaruh Pajak dan Retribusi Daerah terhadap Anggaran Pendapatan dan Belanja Daerah (APBD) Pemerintah Provinsi Jambi - Neng Setiawati; Nadiatul Khoiroh (Universitas Batanghari Jambi, 2022)
This study aims to analyze the effect of regional taxes and retribution on the regional government budget of Jambi Province. The data used in this study is primary data from the Central Bureau of Statistics of Jambi Province and secondary data is carried out by library research obtained from literature, journals and other information related to the issue of Taxes and Retribution.The analytical tools used are Regional Tax Growth Analysis, Regional Retribution Growth Analysis, Contribution/share, and Multiple Regression Analysis.The results showed that the average growth rate of Jambi Provincial Government Regional Tax revenue during 2016-2020 was 8.27 percent. with a growth rate ranging from -2.17 percent to 26.57 percent. Average growth rate of Provincial Government retribution revenue. The average growth rate of regional retribution revenue for the Jambi Provincial Government during 2016-2020 is 7.01 percent. with a growth rate ranging from 5.75 percent to 26.16 percent. The results of the regression calculation show that regional taxes and retribution have no effect on the Jambi provincial government budget.